A review on by-product utilization of plantain - Kumari, Anjana; Rao, Eram S; Agarwal, Aparna (Journal of Postharvest Technology, 2023)
India is the world’s largest banana producer, accounting for 27 percent of global banana production. It’s also the world’s second-most-produced fruit, behind citrus, accounting for around 16% of global fruit production. Plantains are the most well-known of the cooking bananas, accounting for almost one-third of total production. Since most edible bananas are grown primarily for their fruits, banana plantations generate a large amount of waste and by-products. Its vast by-products, which are recycled agricultural waste, offer a fantastic supply of incredibly important raw materials for other enterprises. The methodology of the study involved surveying primary and secondary information generated in the respective field of interest. The articles found most suited for the research problem and objective of the study were selected. The perspectives taken by different studies and researchers were synthesised to generate a solution to the research problems and to bridge the research gaps in the field. This review discusses the utilization of banana by-products such as peels, leaves, pseudostem, stalk, and inflorescence in various food and non-food applications acting as a thickening agent, colouring agent, and flavouring agent, as well as an alternative source of macro- and micronutrients, dietary supplements, animal feed, natural fibres, and organic bioactive substances and bio-fertilizers..